Financiamento da educação superior: aplicação dos recursos da assistência estudantil para o auxílio restaurante universitário - Rodrigues, Ilsy Gisleany de Medeiros (2023)
Following the democratization of higher education, the National Student Assistance Program – PNAES was established in 2007 as a development policy to support students who are at risk of socioeconomic vulnerability and access higher education, providing assistance to these students in the areas of housing, food, health, sport, culture and leisure, transport, among others. In this sense, the aforementioned research aimed to analyze how PNAES resources are applied to aid the university restaurant at the Federal University of Paraíba, collecting data on the operating model of the university restaurant, the history of contracts, as well as data budgets to fulfill this aid. For this purpose, we carried out research, with a qualitative and applied approach, using content analysis of data related to the theme. Data obtained through bidding notices, contracts for the university restaurant, institutional management reports, institutional development plan were analyzed, as well as data obtained through the integrated ombudsman and information access platform – FalaBR and access to the platform integrated equity, administration and contracts system (SIPAC). The results corresponded to a history of contracts for the university restaurant (RU) with periods of contractual suspension in which meals offered to students were replaced for money; With regard to the cost of the RU aid, we found that in addition to the resources coming from PNAES, it was necessary to mobilize resources from other sources to finance it; We also noticed a decrease in the number of students served between 2019 and 2021 for RU Campus I, also followed by a drop in the budget available to fund the program in that period. Therefore, we highlight the importance of PNAES in social inclusion and support for student retention, highlighting the need for robust investments and better applicability of these resources. We realize that it is necessary to optimize outsourcing contracts to ensure continuity and expansion of the scope of aid and we conclude that outsourcing the UFPB university restaurant has its potential, but it is necessary to minimize the risks to the financing of student assistance. Finally, as it is a professional master's degree, the study resulted in the preparation of a situational report, with the purpose of providing the institution with the scenario of university restaurant aid between the years 2016 and 2022.